2012
DOI: 10.1021/ja301586m
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Mechanism of Lithium Ion through Basal Plane of Layered Graphene

Abstract: Coexistence of both edge plane and basal plane in graphite often hinders the understanding of lithium ion diffusion mechanism. In this report, two types of graphene samples were prepared by chemical vapor deposition (CVD): (i) well-defined basal plane graphene grown on Cu foil and (ii) edge plane-enriched graphene layers grown on Ni film. Electrochemical performance of the graphene electrode can be split into two regimes depending on the number of graphene layers: (i) the corrosion-dominant regime and (ii) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
272
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(290 citation statements)
references
References 49 publications
17
272
1
Order By: Relevance
“…Thus, the resulting sample shows a higher reversible capacity as an anode material for LIBs than normal N-doped graphene. The divacancy and Stone-Wales defects inevitably exist in the resulting N-doped graphene analogous particles 57,58 and would be beneficial for the adsorption of Li atoms according to previous reports 59,60 . However, graphene (approximately 568 mA h g À 1 ) (ref.…”
Section: Characterizationmentioning
confidence: 76%
“…Thus, the resulting sample shows a higher reversible capacity as an anode material for LIBs than normal N-doped graphene. The divacancy and Stone-Wales defects inevitably exist in the resulting N-doped graphene analogous particles 57,58 and would be beneficial for the adsorption of Li atoms according to previous reports 59,60 . However, graphene (approximately 568 mA h g À 1 ) (ref.…”
Section: Characterizationmentioning
confidence: 76%
“…The special feature of nanocarbon anode materials is that they exhibit al arger voltage hysteresis between the chargea nd discharge processes than graphite, which resembles hard carbon materials. [14,86,87] Ta ble 1s ummarizes the anode performance with respect to the highlighted electrode materials published in the literature.…”
Section: Nanocarbons As Anodes In Libsmentioning
confidence: 99%
“…Therefore, lithium-ion diffusion through the basal plane cannot exclusively be observed. [73][74][75][76][77] To obtain ac omprehensive pictureo ft he mechanism of lithium diffusion in LIBs, our group fabricated highquality single-layer graphene with aw ell-definedb asal plane (Figure 10 a) and few-layer graphene with an enriched edge plane (Figure10b)t hrough CVD, as indicated in Figure 10 c. [87] We found that Li-ion diffusion perpendicular to the basal plane of graphene is facilitated by defects, whereas diffusion parallel to the plane is limited by steric hindrance originating from aggregated Li ions adsorbed on the abundant defect sites (Figure 10 d). Furthermore,w en oticed that the capacity of the graphene layers decreases continuously as the number of graphene layers increases (Figure 10 d).T his indicates corrosion of the metal current collector and the protective nature of graphene.Wepredicted that the critical layerthickness (l c )tosufficiently prohibit reactiono ft he substrate by using CVD-grown graphene layers is approximately six layers, independent of the defect population on the graphene layers (Figure 10 d).…”
Section: Graphene As An Anode Materialsmentioning
confidence: 99%
“…Particularly, the Li + diffusion mechanism was deeply investigated. [ 75 ] It was demonstrated that Li + diffusion perpendicular to the basal plane of graphene (obtained by CVD) is facilitated by defects, whereas diffusion parallel to the plane is limited by the steric hindrance that originates from aggregated Li ions adsorbed on the abundant defect sites which, also, lead to the previously described drawbacks (i.e., irreversible capacity and voltage hysteresis). Furthermore, the effects on the Li-ion storage properties of different sonication times (for liquidphase-exfoliated graphene), [ 76 ] methods of reduction for graphene oxide [77][78][79][80][81] and electrode preparations [ 82 ] were intensely studied, thus demonstrating again how the processing of this class of materials can strongly infl uence the electrochemical properties of graphene.…”
Section: Continuedmentioning
confidence: 99%